2020
DOI: 10.1186/s40658-020-0284-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a new multipurpose whole-body CzT-based camera: comparison with a dual-head Anger camera and first clinical images

Abstract: Background: Evaluate the physical performance of the VERITON CzT camera (Spectrum Dynamics, Caesarea, Israel) that benefits from new detection architecture enabling whole-body imaging compared to that of a conventional dual-head Anger camera. Methods: Different line sources and phantom measurements were performed on each system to evaluate spatial resolution, sensitivity, energy resolution and image quality with acquisition and reconstruction parameters similar to those used in clinical routine. Extrinsic reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 14 publications
1
36
0
5
Order By: Relevance
“…Among the references, in this study, comparing 111 In-SPECT and 68 Ga-PET, only one ( 6 ) has reported the use of attenuation and PSF correction, remaining authors have not reported any corrections at all, indicating that many comparisons may not have been completely fair. Furthermore, the field of SPECT is developing with new camera designs ( 17 , 18 ) as well as improved reconstruction techniques. Based on the results in this study, a comparison between 68 Ga PET/CT and MC-based reconstruction of 111 In-octreotide SPECT/CT would be of interest to evaluate, both regarding image quality and diagnostic sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Among the references, in this study, comparing 111 In-SPECT and 68 Ga-PET, only one ( 6 ) has reported the use of attenuation and PSF correction, remaining authors have not reported any corrections at all, indicating that many comparisons may not have been completely fair. Furthermore, the field of SPECT is developing with new camera designs ( 17 , 18 ) as well as improved reconstruction techniques. Based on the results in this study, a comparison between 68 Ga PET/CT and MC-based reconstruction of 111 In-octreotide SPECT/CT would be of interest to evaluate, both regarding image quality and diagnostic sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…As patients will probably have multiple 123 I-mIBG scans, it is preferable to keep the cumulative dose as low as reasonably practicable in line with legislation. Perhaps, the future lies in better detector architecture [53].…”
Section: Advances In Technologymentioning
confidence: 99%
“…At present, this technology is being incorporated into general-purpose dual-and multihead SPECT/CT system designs ( Fig. 4) (35,36). Most importantly, reducing image acquisition times and lowering the injected radionuclide activity are now possible for cardiac studies (37) and are being explored for a wider range of nuclear medicine studies.…”
Section: Progress In Physics and Engineering Innovation In Detector Amentioning
confidence: 99%
“…A true paradigm shift in SPECT/CT design was unveiled in 2017, when the first 360°ring-shaped gantry was introduced, equipped with 12 CZT-based elongated detectors that can move inward and outward to come as close to the patient as possible. These detectors are equipped with novel tungsten parallel-hole collimators and move in a swiveling motion to provide a unique scanning geometry (35). Although the clinical experience with this new device is still limited and the additional cost associated with this new design remains to be justified, preliminary results in bone imaging show that a whole-body SPECT acquisition of 20 min offers significant improvements in sharpness and contrast and can replace current bone-scanning protocols (40).…”
Section: The Next Major Leap Forwardmentioning
confidence: 99%